2010
DOI: 10.1016/j.jcrs.2009.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of a handheld digital infrared monocular pupillometer for measurement of the dark-adapted pupil diameter

Abstract: The pupillometer accurately measured the horizontal pupil diameter at 1 lux, with no measurement more than 0.3 mm different from infrared photography measurements. The pupillometer had a slight negative bias that is unlikely to introduce an error greater than 0.5 mm in clinical measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…Several handheld pupillometers that occlude the tested eye are in common clinical use. 1,2 Theoretically, monocular occlusion could artificially enlarge the dark-adapted pupil diameter due to halving of the total retinal light flux. Devices such as wavefront analyzers and topographers incorporate a pupil measurement function [3][4][5] under binocular viewing (both eyes open), but typically the fixation target is no more than 2 feet distant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several handheld pupillometers that occlude the tested eye are in common clinical use. 1,2 Theoretically, monocular occlusion could artificially enlarge the dark-adapted pupil diameter due to halving of the total retinal light flux. Devices such as wavefront analyzers and topographers incorporate a pupil measurement function [3][4][5] under binocular viewing (both eyes open), but typically the fixation target is no more than 2 feet distant.…”
Section: Discussionmentioning
confidence: 99%
“…Details for obtaining 1 lux illumination level in an ordinary eye examination room have been published. 2 Before and during testing, subjects were instructed to maintain steady gaze at the far end of the room (20 feet), which contained no point light sources.…”
Section: Methodsmentioning
confidence: 99%
“…[45][46][47][48][49][50][51][52][53][54] The age related decline in pupil size progresses linearly at an estimated rate of 0.4 mm/decade from the age of 20 years to 90 years. 51,55 However, Bernick suggests that pupillary activity (which is the standard deviation of the mean for each period of stimulation) and the range of pupillary response (which is the difference between the mean response levels in light and dark) may account for some of the relationship between age and pupil size.…”
Section: Fi Gu Rementioning
confidence: 99%
“…Recent studies have shown that the NeurOptics pupillometer provides highly reproducible results comparable with infrared photography and has a high interobserver agreement and repeatability (Schallenberg et al, 2010;Bradley et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…To enhance the signal from the choroid, the "chorioretinal" scanning mode of the instrument was used. (Bradley et al, 2010).…”
Section: Methodsmentioning
confidence: 99%